1997
DOI: 10.1128/jvi.71.2.1466-1475.1997
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of vesicular stomatitis virus mutant polR1 transcription internally at the N gene in vitro

Abstract: The vesicular stomatitis virus (VSV) polymerase is thought to initiate transcription of its genome by first copying a small leader RNA complementary to the 3 end of the template. The polR VSV mutants, in contrast to wild-type virus, frequently read through the leader termination site during transcription in vitro. To shed light on polymerase termination and reinitiation events at the crucial leader-N gene junction, we employed RNase protection assays to precisely measure molar ratios of leader, N, and readthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Experimental support for this model was gathered when an internal polymerase entry site was described to explain VSV-DI particle synthesis (Schubert et al 1979). Furthermore, a mutant version of polymerase was shown to be able to mediate internal entry at the beginning of N gene in vitro (Chuang and Perrault 1997). While, this model lacks supports of experiments done on wild type virus, it was also unable to explain experimentally observed polar transcription in vesiculoviruses.…”
Section: Transcription and Viral Rna Dependant Rna Polymerasementioning
confidence: 89%
“…Experimental support for this model was gathered when an internal polymerase entry site was described to explain VSV-DI particle synthesis (Schubert et al 1979). Furthermore, a mutant version of polymerase was shown to be able to mediate internal entry at the beginning of N gene in vitro (Chuang and Perrault 1997). While, this model lacks supports of experiments done on wild type virus, it was also unable to explain experimentally observed polar transcription in vesiculoviruses.…”
Section: Transcription and Viral Rna Dependant Rna Polymerasementioning
confidence: 89%
“…(4) A spontaneous mutation in the VSV N protein (polR) was found that (i) strongly increases vRdRp read-through of the le/N junction, producing incomplete le/N transcripts of various lengths, and (ii) these mutants synthesizes more N mRNA than le RNA in vitro, in contrast to the wild-type reaction (Chuang and Perrault, 1997). This is the best evidence so far that vRdRp can directly initiate the N mRNA in vitro, at least when the N ass of the template is mutated.…”
Section: Recent Experiments With Vsvmentioning
confidence: 99%
“…Although the precise mechanisms responsible for transcript initiation and termination have not been defined, several different models have been proposed over the last two decades to explain certain features of VSV transcription (2). There is some evidence that the viral polymerase may initiate at internal sites on the genome (7,37), and it has been suggested that the polarity observed during VSV transcription is the result of elongation of internally initiated polymerase complexes being dependent on transcription of the upstream gene (37). However, the most widely accepted model is that the viral polymerase initiates transcription de novo from the extreme 3Ј terminus of the genomic RNA (12) and then genes are sequentially transcribed by a start-stop mechanism (12,20).…”
mentioning
confidence: 99%